Outlook and Prospects of Online Retail Industry in India - Devi, Suman (The journal of contemporary issues in business and government, 2021)
Traditional brick-and-mortar merchants are losing ground to India's well-heeled online marketplaces, which are stealing the thunder (and the revenues). In last five years, internet merchants like as Flipkart, Snapdeal, and Amazon, among others, used heavy discounting to affect brick-and-mortar stores' revenues. The Indian retail industry is undergoing a transformation. In India, e-retailing is still in its infancy, undergoing tremendous transition, challenge, and opportunity in the retail business. Not only metros, but also tier 2 and tier 3 cities are supporting Rapid internet penetration via PCs and mobiles, growing adoption of online medium by brick-and-mortar stores, higher smartphone purchases, the need for ease of shopping, rising real estate prices, and changing consumer preferences are the major drivers of online retail in India, according to the study's findings. The change to omni-channel commerce rather than traditional brick-and-mortar retailing will be the key to survival for today's firms.